"The Intel Microprocessors: 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Pentium Pro Processor, PentiumII, Pentium III and Pentium 4, Architec" - Brey (Barry); Sarma (C R) (2007)
The Intel Microprocessors
20
Keywords: The Intel Microprocessors